Management of Thrombosis in a Patient with Three Thrombophilic Disorders - Marco-Rico A; Mantilla Pinilla AJ; Corral J; Marco-Vera P (Journal of Blood Medicine, 2024)
Ana Marco-Rico,1– 3 Alix Juliette Mantilla Pinilla,2,4 Javier Corral,5 Pascual Marco-Vera2,3 1Thrombosis and Hemostasis Department, Hematology Service, University General Hospital Dr. Balmis, Alicante, Spain; 2Biomedical Health Research Institute (ISABIAL), Alicante, Spain; 3Department of Clinical Medicine, Miguel Hernández University, Alicante, Spain; 4Vascular and Interventional Radiology Department, University General Hospital Dr. Balmis, Alicante, Spain; 5Servicio de Hematología y Oncología Médica, Hospital Universitario Morales Meseguer, Centro Regional de Hemodonación, IMIB, CIBERER-ISCIII, Universidad de Murcia, Murcia, SpainCorrespondence: Ana Marco-Rico, Thrombosis and Hemostasis Department, Hematology Service, University General Hospital Dr. Balmis, Pintor Baeza avenue, 12, Alicante, 03010, Spain, Tel +34 965913863, Fax +34 965913869, Email marco_anaric@gva.esAbstract: Combined thrombophilia represents 7.8– 8.3% of the patients with thrombophilia and confers a higher risk for thrombosis development and recurrence. Here, we present a 17-year-old boy carrier of three congenital thrombophilias, two severe (type I antithrombin deficiency and type I protein S deficiency) and one prothrombotic polymorphism (prothrombin G20210A), all in heterozygosis. He developed an extensive deep venous thrombosis in lower left limb, reaching proximal inferior vena cava and contralateral iliac vein, in the setting of prolonged rest. Endovascular therapy with local thrombolytic agent infusion followed by mechanical thrombectomy was performed, achieving a favorable clinical and radiological evolution. Antithrombin replacement to achieve levels between 80% and 120% with heparin administration was used during the endovascular procedure. The patient is currently asymptomatic and maintains indefinite anticoagulation with warfarin, keeping an appropriate anticoagulation range (international normalized range between 2.5 and 3.5).Keywords: combined thrombophilia, deep venous thrombosis, inferior vena cava, endovascular therapy, anticoagulation